Cognitive information systems in management sciences - Ogiela, Lidia (Intelligent data centric systems., 2017)
Cognitive Information Systems in Management Sciences summarizes the body of work in this area, taking an analytical approach to interpreting the data, while also providing an approach that can be used for practical implementation in the fields of computing, economics, and engineering. Using numerous illustrative examples, and following both theoretical and practical results, Dr. Lidia Ogiela discusses the concepts and principles of cognitive information systems, the relationship between intelligent computer data analysis, and how to utilize computational intelligent approaches to enhance information retrieval. Real world implantation use cases round out the book, with valuable scenarios covering management science, computer science, and engineering. Indexing: The books of this series are submitted to EI-Compendex and SCOPUS Discusses the basic concepts and principles in cognitive information systems, providing 'real-world' implementation examples Explains the relationship between intelligent computer data analysis and how to utilize computational intelligent approaches to enhance information retrieval Provides a unified structured approach that can be used to develop information flow in cognitive management systems.